MEMBANGUN HIPOTESIS DARI PUNCAK KEBUDAYAAN AWAL HOLOSEN DAN NEOLITIK DI SUMATRA BAGIAN UTARA - Ketut Wiradnyana (Forum Arkeologi, 2014)
Reconstruction of early Holocene and Neolithic culture which covers technology, social, and religious aspect is often done partially, considering that the researches and the results obtained are very limited. This study aims to find out a specific description of technology, social, and religious aspects from early Holocene until Neolithic period which became the pinnacle of culture of the period mentioned in order to construct a hypothesis regarding to human adaptation. Those aspects can be identified through archaeological remains obtained from excavation. The analysis of artefact, ecofact, and feature was done through morphology and technology analysis. Interpretation of data was done based on analogy with other similar finds which has the same period. Those approaches will show information regarding to the pinnacle of culture from each period in order to generate a synthesis and renew the old concept. The result of this study is a hypothesis regarding to human adaptation toward their environment in order to fulfil their needs of food and religion. Rekonstruksi budaya masa awal Holosen dan Neolitik yang meliputi aspek teknologi, sosial dan aspek religi kerap tidak lengkap, mengingat penelitian dan hasil yang didapatkan masih sangat terbatas. Tulisan ini bertujuan untuk mengetahui gambaran spesifik unsur teknologi, sosial, dan religi dari masa awal Holosen hingga Neolitik yang merupakan keunggulan budaya masa lalu untuk membangun hipotesis mengenai adaptasi antarmanusia dan lingkungan. Aspek tersebut dihasilkan dari serangkaian ekskavasi, dengan mengidentifikasi aspek morfologi dan teknologi artefak, ekofak, dan fitur, untuk selanjutnya dilakukan analisa. Interpretasi atas data awal tersebut didasarkan juga atas analogi dengan temuan sejenis pada periode sezaman. Metode tersebut menghasilkan berbagai informasi puncak kebudayaan pada setiap periode yang akhirnya menghasilkan sintesa untuk memperbarui konsep lama. Kajian ini menghasilkan hipotesis yang berkaitan dengan adaptasi manusia terhadap lingkungan dalam memenuhi kebutuhan pangan dan religinya.